Analisis Kinerja Pembudidaya Ikan Air Tawar Pada Kelompok Pembudidaya Ikan Purwa Mina Sejati, Banyumas - Hariski Nur Setiawan; Sodik Dwi Purnomo; Diah Retnowati; Zumaeroh Zumaeroh; Damar Jati; Anisa Fatmawati (FEB UNWIKU PURWOKERTO, 2022)
This study aims to analyze the income, efficiency, welfare of freshwater fish farming in the Purwa Mina Sejati Cultivator Group, Banyumas. This research is a quantitative research. The research population was the Fish Cultivation Group (POKDAKAN) of Purwa Mina Sejati, Beji Village, with 25 people. The results showed that (1) The income of freshwater fish farming business in Purwa Mina Sejati Banyumas Cultivator Group was profitable with an income of Rp. 7,604,386.6/month; (2)The freshwater fish farming business of Purwa Mina Sejati Banyumas Cultivator Group has been efficient with the results of the calculation of the R/C ratio of 4.44;(3) Freshwater fish cultivators in Purwa Mina Sejati Cultivation Group, Banyumas are already prosperous with the income of members/families of Rp. 3,213,849.20 greater than the standart living cost of Banyumas district. Keywords: Income, Efficiency, Welfare, Fish Farming